Enhancing Miscanthus floridulus remediation of soil cadmium using Beauveria bassiana FE14: Plant growth promotion and microbial interactions - Ying Wang; Sha Xiang; Rui Chen; Liang Chen; Wendi Lan; Jun Fang; Yunhua Xiao (Ecotoxicology and Environmental Safety)
Soil heavy metal pollution presents substantial risks to food security and human health. This study focused on the efficiency of plant growth-promoting fungus-Beauveria bassiana FE14 and Miscanthus floridulus on the synergistic remediation of soil Cd contamination. Results revealed that B. bassiana FE14 significantly enhanced the growth of M. floridulus, substantially decreased Cd content in soil by 79.39 %, and modified enzyme activities (superoxide dismutase, peroxidase, and catalase) to alleviate Cd-induced oxidative stress in plants, determined by the physical and chemical indicators and enzyme activities of soil and plant. Based on microbiome analysis, this study also found significant changes in the composition, structure, and molecular ecological network of endophytic bacterial communities in roots, but this study had little effect on the bacterial and fungal communities in rhizosphere soil. In addition, the key genera (including Sphingomonas, unclassified_Comamonadaceae, Massilia, Bradyrhizobium, and Paraglomus) and key genes/enzymes (including cadC, zinc transporter, zinc and cadmium transporter, exoZ/Y/Z, catalase-peroxidase, superoxide dismutase, nitrite reductase, acid phosphatase, etc.) were involved in promoting plant growth and alleviating Cd stress. These findings revealed the potential of B. bassiana FE14 and M. floridulus working in synergy to enhance the phytoremediation efficiency of Cd-contaminated soils, thus presenting a promising approach for integrated plant-microbe remediation strategies.